1981
DOI: 10.1002/1097-0142(19810215)47:4<645::aid-cncr2820470404>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Adriamycin/cis-platinum/cyclophosphamide combination chemotherapy for advanced carcinoma of the parotid gland

Abstract: Five patients were treated with a combination of Adriamycinlcis-platinumlcyclophosphamide for far-advanced and/or recurrent cancers of the salivary gland. Adriamycin, 40 mglm', and cis-platinum, 50 mg/mf, were given on day 1; cyclophosphamide, 200 m g h ' daily for four days, was given by mouth on the third to sixth day of each monthly therapy course. Two patients achieved a complete remission, each lasting five months, and the three others had partial remissions from one to seven months (median six months) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 4 publications
1
27
0
Order By: Relevance
“…They also achieved a partial response in three and six patients respectively with a median duration of 6 months in both groups. Other studies (Budd & Groppe, 1983;Vermeer & Pinedo, 1979;Alberts et al, 1981;Tannock & Sutherland, 1980) reported partial responses with median durations of 5 weeks, 5 months, and 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They also achieved a partial response in three and six patients respectively with a median duration of 6 months in both groups. Other studies (Budd & Groppe, 1983;Vermeer & Pinedo, 1979;Alberts et al, 1981;Tannock & Sutherland, 1980) reported partial responses with median durations of 5 weeks, 5 months, and 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Rentschler et al, 1977;Johnson et al, 1964;Alberts et al, 1981;Skibba et al, 1981;Creagan et al, 1983;Richards & Chambers, 1973;Moore et al, 1968). Some of these studies are case reports and some are trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Response rates seem diminished in adenoid cystic carcinoma and when used as second or third line therapy. In the study showing a 100% response rates, only 5 patients were enrolled [46].…”
Section: Conventional Therapymentioning
confidence: 99%